Social Inclusion in Macro-Level Diagnostics : Reflecting on the World Bank Group's Early Systematic Country Diagnostics - Das, Maitreyi Bordia (World Bank, Washington, DC, 2016)
The idea of social inclusion has garnered considerable attention, especially in the context of two recent developments: the Sustainable Development Goals and the heightened attention to inequality. This paper reviews the manner and extent to which social inclusion is addressed in the first 17 Systematic Country Diagnostics (SCDs), which are ex ante, country-level assessments conducted by the World Bank Group, ahead of the preparation of its Country Partnership Frameworks. In addition to this primary purpose, the paper fulfils three other purposes. It allows for a broader reflection on the value of the social inclusion construct in macro-level diagnostics; it takes the opportunity to develop and refine a methodology to assess social inclusion and finally, it positions the narrative on social inclusion into the ongoing discourse on poverty, shared prosperity, inequality and the thinking around the implementation of the Sustainable Development Goals. It is therefore, a refined articulation of the idea of social inclusion in the context of global epistemological shifts